THE SYSTEM OF DETERMINING SUBSIDIZED FERTILIZER RECIPIENTS FOR COFFEE FARMERS BY THE BENER MERIAH AGRICULTURE AND PLANTATION OFFICE ACCORDING TO THE CONCEPT OF AT-TAS'IR AL-JABARI - Yusriga; Ramli, Misran (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2026)
The construction of the Wastewater Treatment Plant (WWTP) in Aceh Tengah Regency is a strategic government project implemented through a construction service contract between the P2P Work Unit as the project owner and PT Meudang Pirak as the service provider. During its implementation, the project encountered various technical and non-technical constraints that resulted in contract changes through three addendum contracts. This condition raised legal issues regarding the validity of the addendum contracts under both positive law and the perspective of Islamic jurisprudence (fiqh muamalah), particularly within the framework of the ijārah 'ala al-'amāl contract. Therefore, the research problems of this study focus on the validity of the main contract and its addendums in the Aceh Tengah WWTP project and their conformity with the principles of ijārah 'ala al-'amāl. This study employs a qualitative method with a descriptive-analytical approach through library research by examining contract documents, statutory regulations, and relevant fiqh muamalah literature. The findings indicate that all addendum contracts implemented constitute legally valid contractual adjustments from administrative, juridical, and sharia perspectives, as they do not eliminate the pillars and conditions of the ijārah contract. Instead, the addendums function to maintain contractual continuity, ensure clarity of the work object, guarantee certainty of ujrah (wages), and realize the principles of justice and public benefit (maṣlaḥah). Accordingly, the main contract and its addendums in the Aceh Tengah WWTP project are deemed valid and consistent with both positive law and Islamic jurisprudence